Effectiveness of Concept Change Oriented Learning with Dual Situated Learning Model (DSLM) Assisted by Multi Representations (MRs) To Improve Understanding of Acid-Base Concepts for High School Students - Yahmin; Urwatil Wutsqo Amry; Sri Rahayu (Journal of Multidisciplinary Science, 2025)
Research on the Effectiveness of Concept Change Oriented Learning with Dual Situated Learning Model (DSLM) Assisted by Multi Representations (MRs) to Improve Acid-Base Concept Understanding of High School Students is a quantitative study which employs a quasi-experimental design with a non-equivalent control group design pretest-posttest. The research subjects were 70 students of class XI pattern 5 SMAN 4 Malang for the academic year 2020/2021 which comprised two classes taken by cluster random sampling, one class as the control class (34 students) and one class (36 students) as the experimental class. The research data was collected using the acid-base concept understanding test instrument (TPKAB) which comprised 25 items (17 items for two-tier questions and 8 items for multiple choice). The research hypothesis was examined through the ANCOVA test assisted by the SPSS 21.0 for windows program with a significance level of = 0.05. The results demonstrated the increase in the average value of the experimental class was higher than the increase in the average score of the control class after learning acid-base material. Meanwhile, the results of the delay-test demonstrated the PK-DSLM-MRs were effective in maintaining the retention of students' conceptual understanding on acid-base material. PK-DSLM-MRs gave the strongest influence on the group concept of acid-base strength. The number of misconceptions and students who experience misconceptions in the control class is more than the number of misconceptions and students who experience misconceptions in the experimental class.